THE INFLUENCE OF HUMAN RELATIONS AND ISLAMIC WORK ETHIC ON EMPLOYEE PERFORMANCE AT LAZISMU PURWOREJO REGION - Nenden Nur Annisa; Meriam Esterina; Fitria Amallia; Rizky Risma Cahyani (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study aims to determine the effect of human relations, Islamic work ethic and employee performance at LAZISMU Purworejo Region .The population of this research is LAZISMU Purworejo Region employees from various ranks/classes. The sampling technique used is random sampling. Data related to research variables were collected using questionnaires distributed to all respondents and filled out by respondents themselves based on respondents' perceptions. Based on the instrument test conducted, it is proven that all statement items in the questionnaire are proven to be valid and reliable. The analytical technique used to prove the hypothesis is multiple linear regression. The results showed that Human Relations did not have a positive and significant effect on employee performance. Islamic work ethic has a positive and significant effect on the performance of LAZISMU Purworejo Region employees. Suggestions that can be given to LAZISMU Purworejo Region is to keep paying attention to Human relations (relationships between humans) where the relationship or cooperation between two or more individuals, especially in relationship status or social interaction and good social communication can certainly affect an individual's performance in complete tasks assigned by superiors. The better the level of human relations between employees, superiors, and customers, the better the performance of employees. Furthermore, the management of LAZISMU Purworejo Region also needs to improve the existence of a high work ethic in employees where the work ethic will make the employee effective at work. The better the Islamic work ethic, the better the performance of employees Keywords: Human Relations, Islamic Work Ethic, Employee Performance